Structural characteristics of adlayer in heterogeneous catalysis. (22nd October 2016) - Sun, Fei; Huang, Wen Lai; Li, Jinghai
Abstract: This paper explores the adsorbate distributions in the adlayer for a model system of heterogeneous catalysis, A+B→AB. Relevant kinetic mechanisms are revealed in terms of Shannon entropy via kinetic Monte Carlo (KMC) simulations. It is reckoned that reactions account for the clustering of the adsorbates, whereas diffusion and desorption tend to homogenize the adsorbate distribution besides adsorption, and diffusion exhibits a relatively stronger role. The clustering tendency seems to compete with the homogenizing one, showing alternate dominance in microscale space and time. The compromise between these two tendencies was reflected as the extremal tendencies at the mesoscale and the macroscale. However, such extremal tendencies can be maximization or minimization of Shannon entropy, depending on the choice of the initial state, implying the insufficiency of a single extremal function of Shannon entropy. Graphical abstract: Highlights: The kinetic mechanisms for adsorbate distributions are revealed. Shannon entropy is employed to characterize the structures in the adlayer. Competing tendencies for different phases in the adlayer are explored. Competition was observed at the microscale. Compromise was unraveled at the mesoscale and macroscale.